The Correlation of Knowledge and the Attitudes of Class VII Teenage Girls in Readiness to Face Menarche - Mulazimah Mulazimah; Dhewi Nurahmawati; Indri Hapsari Trishastuti (Journal of Ners and Midwifery, 2022)
Menstruation is one of the things that many girls or teenage girls fear. Those who are not aware of the occurrence of changes in the body and its reproductive processes, can suppose that menstruation is one of the diseases that occurs on her that affects physical and mental health.Â  It happens to girls who are not given the knowledge and understanding of the correct menstruation, that menstruation is as a normal function. teenage girls who are not ready to face menarche will experience fear, anxiety, surprise, sadness, disappointment, shame, worry and confusion that will arise the desire to reject the physiological process. Adolescence feels that menstruation as something cruel and threatening, this can also continue in a more negative direction. Teenage girls who are ready to face menarche, will feel happy and proud, because they consider themselves biologically mature. Analytical observational research with cross sectional design.Â  The subjects in this study were teenage girls in grade VII of SMPN 1 Gampeng Rejo Kediri who were aged 12-14 years and were willing to become respondents, who had not or who had menstruated and wanted to fill out the questionnaires included in the inclusion questionnaire totaling 40 people. Most of the 29 respondents (72.5%) had an attitude of accepting criteria to face menarche, namely 2 respondents (5%) with criteria not ready to face menarche, 16 respondents (40%) with criteria of being sufficiently prepared and 11 respondents (27.5%) with ready criteria. The results of the correlation test showed there is a significant relationship between the Menarche Knowledge and Attitudes of Class VII Teenage Girls in Menarche Readiness.Â  D gets a value of Ïvalue = 0.000 < Î± 0.05.